Considerations on the Equalization the Legal Position of Churches and Other Religious Organizations and Non-Confessional Organizations - Bernaciński, Łukasz (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
This chapter is an attempt to answer the question about the existence of premises supporting the obligatory equalization of the legal position of churches and other religious organizations and nonreligious ideological organizations. For this purpose has analyzed the legal status of entities, the attitude of the European Union to the discrepancies occurring in this field and the functions that the entities fulfill towards their members. Context for considerations are bills created in the years 2013–2019, concerning the replacement of the Church Fund tax write-off for churches and other religious organizations, and granting to nonreligious ideological organizations the right to a permanent, institutional dialogue with the state.